John Locke critical assessments - Ashcraft, Richard (Critical assessments of leading political philosophers., 1991)
Designed to provide students and researchers in political theory and philosophy with access to Locke's entire contribution to political philosophy, this major reference work stresses the development of the principles upon which the American Constitution and the French Revolution were based.